Day time sleepiness in medical undergraduates: social media the culprit? - Lakshmi, Vijaya; Jindal, Manisha; Nanda, Bijli (International Journal of Advances in Medicine, 2018)
Background: Medical undergraduates have been seen to be suffering from sleep disturbances, especially daytime sleepiness. Social Media usage or social networking has also tremendously increased over the past few years in adolescents. It has also increased in the day-to-day lives of medical students. Authors therefore tried to find out the association, if any, between social Media usage and daytime sleepiness in medical undergraduates and whether daytime sleepiness can affect their academic performance. The objective of the present study was to ascertain the association between daytime sleepiness and usage of social media among medical students and to look for any association of daytime sleepiness with academic performance. Methods: A self-administered, questionnaire-based study was conducted on medical undergraduate students to assess social media usage. Epworth sleepiness score was determined. ‘Analysis of variance’ was done to look for any association between (a) social media usage and daytime sleepiness (b) daytime sleepiness and academic performance. Results: The majority of students (77.14%) used social media for 2-5hours per day and whatsapp was the most commonly used medium by them. Highly significant association was observed between the usage of social media and daytime sleepiness among the medical undergraduates. Daytime sleepiness was also significantly related to the academic performance of the participating students. Conclusions: Sleep disturbance particularly daytime sleepiness is significantly associated with the usage of social media among first year medical undergraduates and can significantly affect their academic performance.